Determining optimal treatment strategy for diffuse glioma: the emerging role of IDH mutations. Issue 6 (June 2015) - Juratli, Tareq A; Cahill, Daniel P; McCutcheon, Ian E
<x xml:space="preserve">Abstract</x> The isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) genes mutate frequently in gliomas, and it has become increasingly apparent that IDH mutation status accounts for much of the prognostic information previously rendered by histological grading. Most glioblastomas (90–95%) are IDH wild-type and most lower-grade diffuse gliomas (80%) are IDH-mutant. We examine here how IDH mutation status interacts with treatments known to influence survival (surgery, chemotherapy and radiotherapy) in patients with gliomas, and the impact of the IDH mutations on patients' survival after such treatments. IDH mutations is associated with more complete surgical resection of enhancing disease, and with a better response to RT. In addition, there is increasing clinical evidence that, in certain contexts, IDH mutations predict chemotherapeutic sensitivity. Mutations in IDH and other genes are beginning to drive decisions on therapy for diffuse gliomas and will likely allow tailoring of treatment by molecular profile in the future.